Analysis Of Medicinal Chemicals In Uric Acid Jamu Using The Thin Layer Chromatrography - Safrina (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Indonesian people tend to use medicines made from natural ingredients to maintain a healthy body. Based on traditional medicine laws and regulations, it is prohibited to use isolated or synthetic chemicals with medicinal, narcotic, or psychotropic properties, as well as ingredients from protected animals or plants. However, there are still many jamu that contain medicinal chemicals that are freely circulating on the market. This study aims to analyze the medicinal chemicals of allopurinol, prednisone, and dexamethasone in jamu for gout circulating in Banda Aceh using the thin layer chromatography (TLC) method. This research is experimental in nature and involves qualitative laboratory tests with three samples of gout jamu taken based on the purposive sampling method with three repetitions of observations on TLC carried out by looking at the spots under a 254 nm UV lamp, then comparing the Rf value between the test solution and the sample solution. Based on the results of observations from both methods, it is suspected that the three negative samples contained medicinal chemicals such as allopurinol and prednisone because the Rf values were different between the working standards and the samples. The positive dexamethasone occurred in the three jamu. This is not in accordance with the regulation of the Minister of Health of the Republic of Indonesia number 007 of 2012 concerning registration of traditional medicines, which states that traditional medicines are prohibited from using isolated chemicals, which are often called medicinal chemicals.